It's Harder to Push, When I Have to Push Hard—Physical Exertion and Fatigue Changes Reasoning and Decision-Making on Hypothetical Moral Dilemmas in Males - Weippert, Matthias; Rickler, Michel; Kluck, Steffen; Behrens, Kristin; Bastian, Manuela; Mau-Moeller, Anett; Bruhn, Sven; Lischke, Alexander (Frontiers in Behavioral Neuroscience, 2018)
Despite the prevalence of physical exertion and fatigue during military, firefighting and disaster medicine operations, sports or even daily life, their acute effects on moral reasoning and moral decision-making have never been systematically investigated. To test the effects of physical exertion on moral reasoning and decision-making, we administered a moral dilemma task to 32 male participants during a moderate or high intensity cycling intervention. Participants in the high intensity cycling group tended to show more non-utilitarian reasoning and more non-utilitarian decision-making on impersonal but not on personal dilemma than participants in the moderate intensity cycling group. Exercise-induced exertion and fatigue, thus, shifted moral reasoning and moral decision-making in a non-utilitarian rather than utilitarian direction, presumably due to an exercise-induced limitation of prefrontally mediated executive resources that are more relevant for utilitarian than non-utilitarian reasoning and decision-making.